2020
DOI: 10.1177/2059700220924499
|View full text |Cite
|
Sign up to set email alerts
|

Concussion disclosure in middle and high school youth: Who gets the message and are they trained to receive it?

Abstract: Background Disclosure of concussion is vital for proper diagnosis and treatment. Youth have many stakeholders to whom they may disclose concussion, including parents, peers, coaches, and school personnel. We examined whom high school and middle school youth report concussion and the level of concussion education of the recipients of the disclosure. Methods Data were analyzed from 2362 students, 680 parents, and 150 school personnel who completed an online survey about concussion reporting, education, and train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Third, the lack of knowledge of concussion policy does not equate to the lack of knowledge on concussion. However, we have previously shown that in addition to not knowing about school policy, parents are less educated on topics related to concussion than school personnel, for example (Wicklund & Coatsworth, 2020). While analysis of policy content is beyond the scope of this article, other research has demonstrated significant variability in the school concussion policy even within the same states (Coxe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the lack of knowledge of concussion policy does not equate to the lack of knowledge on concussion. However, we have previously shown that in addition to not knowing about school policy, parents are less educated on topics related to concussion than school personnel, for example (Wicklund & Coatsworth, 2020). While analysis of policy content is beyond the scope of this article, other research has demonstrated significant variability in the school concussion policy even within the same states (Coxe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear from the findings in this study whether the higher prevalence of self-reported sports- self-reported sports- or physical activity–related concussion among middle students was driven primarily by a greater susceptibility to brain injury due to neurobiological factors, 1 differing reporting behaviors between middle and high school students, 47 or other factors that may affect concussion rates (eg, participation in team sports and physical activity, 13 exposure to multiple sources of concussion education, 41 and social ecological factors 23,42 ). Future studies could explore these factors and inform concussion safety interventions for middle school students.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, younger athletes more often report their suspected concussion to their parents, who receive less concussion specific training; whereas, older high school athletes more often report to coaches and athletic trainers. 8 Therefore, recepients of disclosure may also influence concussion diagnosis, especially in younger athletes. Importantly, despite initial investigations of athletic injury at the youth level, 22 more studies investigating the epidemiology of injury in youth sports would add to our understanding of the burden of concussion in youth athletes and direct preventative efforts in this setting.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%